Fatwa Dan Politisasi Agama (Analisis Wacana Penggunaan Fatwa Pada Pilkada DKI Jakarta) - Abdillah Halim (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
The use of fatwa to delegitimize the constitutional rights of citizens to compete in a healthy manner in filling in public positions as occurred in the 2017 DKI Jakarta Pilkada is a form of injustice and manipulation. The fatwa which is actually not binding is then forced through the discourse strategy until the emphasis and mass action. In this paper, the phenomenon is examined with a critical discourse analysis tool in order to analyze the practice of acting that reflects social problems, relativize the practice of ideological mystification in fatwas, ignite public awareness of injustice and marginalization in the use of fatwas, and finally find solutions to overcome them. This paper shows that there has been a politicization of religion in the use of fatwas in the 2017 DKI Jakarta Pilkada. The politicization of religion through fatwas is a political practice that must be avoided, various solutions to overcome it, as contained in this paper, need to be further elaborated and executed.Â